Effects of Oceanic Crustal Thickness on Intermediate Depth Seismicity - Wagner, Lara S.; Caddick, Mark J.; Kumar, Abhash; Beck, Susan L.; Long, Maureen D. (Frontiers in Earth Science, 2020)
The occurrence of intermediate depth seismicity (70 – 300 km) is commonly attributed to the dehydration of hydrous phases within the downgoing oceanic plate. While some water is incorporated into the oceanic crust at formation, a significant amount of water is introduced into the plate immediately before subduction along outer-rise faults. These faults have been shown to extend to depths of over 30 km and can channel water to depths of 20 km or more beneath the seafloor. However, the amount of water introduced into the oceanic mantle lithosphere, and the role of that water in the formation of intermediate depth seismicity, has been the topic of ongoing research. Here we compile evidence from areas where the subducted oceanic crust is likely thicker than the penetration depth of water into the downgoing plate. These regions comprise aseismic plateaus and ridges (hot spot tracks) that can be compared directly to adjacent segments of the oceanic plate where oceanic crust of normal thickness is subducted. Regions with thick oceanic crust show little to no seismicity at intermediate depths, whereas adjacent regions with normal oceanic crust (~6-8 km thick) have significant seismicity at similar depths and distances from the trench. We hypothesize that intermediate depth earthquakes observed in regions with thinner oceanic crust are caused by mantle dehydration reactions that are not possible in regions where the oceanic mantle was never hydrated because the thickness of the oceanic crust exceeded the penetration depth of water into the plate. We compare our observations to phase diagrams of hydrous basalt and depleted peridotite to determine pressures and temperatures that would be consistent with our observations. These can provide valuable constraints, not only on the degree of hydration and dehydration in the downgoing plate, but also as ground-truth for thermal models of these regions, all of which have complex, three-dimensional, time-variant subduction geometries and thermal histories.